Influence of Wall Teichoic Acid on Lysozyme Resistance in Staphylococcus aureus - Bera, Agnieszka (American Society for Microbiology, 2007)
Staphylococcus aureus peptidoglycan (PG) is completely resistant to the hydrolytic activity of lysozyme. Here we show that modifications in PG by O acetylation, wall teichoic acid, and a high degree of cross-linking contribute to this resistance.